Green Synthesis of New Heterocyclic Surfactant Compounds by Multicomponent Reactions and Their Antibacterial and Corrosion Inhibitor, Study on Carbon Steel Alloy in Acid Media 2 M HCl - Raneen Salim Al-Hilfi; Najlaa Zaki Al-Ameri; Mouhanad Jwad Al-Asadi (Universitas Gadjah Mada, 2023)
Heterocyclic 1,4-di(1,3,5-dithiazinan-5-yl)benzene (D) and two heterocyclic-cationic Gemini surfactant 5,5'-(1,4-phenylene)bis(5-decyl-1,3,5-dithiazinan-5-ium)bromide (E) and 5,5'-(1,4-phenylene)bis(5-tetradecyl-1,3,5-dithiazinan-5-ium)bromide (F) were prepared and identified by FTIR, 1H-NMR spectroscopies, and GC–MS. Then, they were tested as corrosion inhibitors against carbon steel corrosion in 2.0 M aggressive HCl medium at 25 and 50 °C. They have different carbon chain tails, i.e., E (10 carbons), and F (14 carbons). These new heterocyclic and surfactant categories as corrosion inhibitors. The corrosion process has been studied electrochemically (Tafel Plot). The inhibition efficiency clarified that the decrease in IE(%) is in the order of F > E > D. The biological activity of compounds D and F was investigated using the aforementioned drilling procedure with a cork drill. At a dosage of 3000 mcg/mL, the biological action of compound D demonstrated effective resistance against the two types of negative bacteria. The cation has a diameter of 20 mm against E. coli and 19 mm against S. epidermis bacteria. At the same concentration, the chemical F is solely effective against E. coli with an inhibition diameter of 14 mm.